Crise, urbano e revolta: as Jornadas de Junho de 2013 - Manuela Mendonca de Alvarenga (2016)
This work consists of a set of questions raised from the protests of June 2013 (known as "Jornadas de Junho" in Brazil). Viewed as an urban event, the protests paved the way, due to their contradictions and political developments, to a number of interpretations regarding the Brazilian and global reality. Commonly seen as a breaking point which opened the way of a "political crisis", added to a series of other "crises"; or as one more element to add to the "perfect storm" that supposedly reached Brazil on a sudden way, this event requires a theory beyond its immediate time-space occurrence. In this sense a hypothesis arises: the event of June 2013 is a form of expression of the process of the urbanization of society and henceforth is at the same time form of concrete expression of the crisis of capitalism and the resistance to it in a "blind field". With topics running through important debates of the critical theory of society, we seek to think the (mis)direction of revolutionary thought in a "time of decreasing expectations". Transversely, the concepts of crisis and urban blend together as constituents of the capitalist mode of production, always in a contradictory movement that erupts in enigmatic acts of protest in dark times.